Bridging the distance: understanding access to healthcare through stories from Gwich’in medical travellers in Northwest Territories - Crystal Milligan; Sharla Greenland; Lorna Storr; Agnes Pascal; Stephanie Irlbacher-Fox; Mark J. Dobrow (International Journal of Circumpolar Health)
In northern Canada, medical travel – the movement of patients to a larger centre to access healthcare services outside their home community – is a dominant feature of the healthcare system. This qualitative study explored the medical travel experiences of Gwich’in living above the Arctic Circle in the Gwich’in Settlement Area in Northwest Territories (NT). Data collection in 2020 comprised storytelling sessions with 10 Gwich’in medical travellers (6 female, 4 male). Using inductive and deductive methods with continual critical reflexivity, and guided by Gwich’in values, concerns about access to healthcare were found to be at the heart of each story. A broad conceptualisation of access was applied to understand and interpret the results according to six dimensions: accessibility, availability, affordability, adequacy, acceptability, and awareness. Situated within a context of colonialism, structural inequities and other factors relevant across the Circumpolar North, the results suggest that the NT medical travel policy framework provides only partial access to care. This article illustrates a need for healthcare and other government systems to think about policy and programmes in a more wholistic, equitable and relationship-centred way, which would help not only to bridge distances across geography, but also between peoples.